PELESTARIAN GAMBANG KROMONG: MENJAGA TRADISI MUSIK MELALUI PENDIDIKAN NON FORMAL - Muhammad Zidhan Assidiq; Sandie Gunara; Febbry Cipta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Gambang Kromong is one of the traditional Betawi musical art forms that has a very important cultural value. However, in the midst of modernization, its existence is increasingly marginalized. This research aims to explore the role of informal education in maintaining and preserving the art of Gambang Kromong as part of the Betawi cultural tradition. This research applies a descriptive-analytic method with a qualitative approach, data obtained using observation, interview, documentation, and document study techniques. The research was conducted at the Gitarda Art Studio located in Bekasi, where Gambang Kromong traditional music training is organized in the context of out-of-school education. The results showed that music teaching and learning activities took place in an interactive and innovative manner, where Sanggar Seni Gitarda played an important role in preserving Gambang Kromong. The studio successfully incorporates cultural values into the learning process and collaborates with local communities to organize cultural events, which are effective in fostering young people's interest in traditional Betawi music.